2011 IEEE Virtual Reality Conference 2011
DOI: 10.1109/vr.2011.5759484
|View full text |Cite
|
Sign up to set email alerts
|

A design for a smartphone-based head mounted display

Abstract: Thin computing clients, such as smartphones and tablets, have experienced recent growth in display resolutions and graphics processing power. In this poster, we show how to leverage these trends to create an experimental wide field of view, 3D stereoscopic head mounted display (HMD), based on two high resolution smartphones. This HMD prototype is unique in that the graphics system is entirely onboard, allowing it to be lightweight, wireless, and convenient to use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 5 publications
0
13
0
2
Order By: Relevance
“…Similar to the design of Olson et al [2011] and the Oculus Rift, this assembly holds a pair of aspheric magnifying lenses (ElectroOptix, Inc. AHM-5). The lenses are separated from the top LCD by slightly less than their 5.1 cm focal length in order to synthesize a magnified, erect virtual image appearing near "optical infinity".…”
Section: Head-mounted Display Resultsmentioning
confidence: 99%
“…Similar to the design of Olson et al [2011] and the Oculus Rift, this assembly holds a pair of aspheric magnifying lenses (ElectroOptix, Inc. AHM-5). The lenses are separated from the top LCD by slightly less than their 5.1 cm focal length in order to synthesize a magnified, erect virtual image appearing near "optical infinity".…”
Section: Head-mounted Display Resultsmentioning
confidence: 99%
“…Failed attempts at VR systems by Nintendo (Virtual Boy) and Sega (Sega VR) in the 1990s and a further lack of development into the 2000s had many of its critics arguing the technology was "dead" [3]. However, as noted by Olson [4] the video games industry has driven advances in graphics cards that are able to handle increasingly sophisticated 3D constructed environments. Furthermore, simultaneous developments in smartphones and HMDs have made VR an accessible commodity for consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Projects such as the FOV2GO project from the MxR lab at University of Southern California [1] [11], demonstrate their potential for use in VR systems. Recently Basu et al [3], have demonstrated a mobile VR system using a phone as a component.…”
Section: Introductionmentioning
confidence: 99%